Interleukin-6 Is an Early Plasma Marker of Severe Postoperative Complications in Thoracic Surgery: Exploratory Results From a Substudy of a Randomized Controlled Multicenter Trial. (January 2022) - Neff, Thomas A.; Braun, Julia; Rana, Dhanu; Puhan, Milo; Filipovic, Miodrag; Seeberger, Manfred; Stüber, Frank; Neff, Simona B.; Beck-Schimmer, Beatrice; Schläpfer, Martin
Abstract : BACKGROUND: Postoperative complications in surgery are a significant burden, not only for the patients but also economically. While several predicting factors have already been identified, it is still not well known if increased levels of inflammatory markers in the immediate perioperative phase correlate with a higher incidence of postoperative complications. This study aimed to evaluate which patient characteristics and intraoperative parameters correlate with increased plasma values of monocyte chemoattractant protein 1 (MCP-1) and interleukin 6 (IL-6) of thoracic surgery patients. A second goal was to explore whether MCP-1 and IL-6 are associated with the incidence of postoperative complications. We hypothesized that there is a positive association between inflammatory markers and the occurrence of complications within 6 months after surgery. METHODS: This is a substudy of a recent randomized controlled trial, which defined the effect of desflurane versus propofol anesthesia on morbidity and mortality in patients undergoing thoracic surgery. MCP-1 and IL-6 were determined in plasma obtained before and 30 minutes after 1-lung ventilation, 6 hours after surgery, and on postoperative days 1 and 2. Complications were recorded for 6 months. Mixed linear models were used to examine factors associated with MCP-1 and IL-6 levels. Logistic regression models and receiver operating characteristic curves were used to determine the association between MCP-1 and IL-6 and postoperative complications. RESULTS: In the original study, 460 patients were included, MCP-1 and IL-6 levels were determined in 428 patients. MCP-1 was positively associated with the duration of surgery ( P = .016), whereas IL-6 levels increased with both the length ( P < .001) and invasiveness of lung surgery (thoracoscopic wedge resection or lobectomy versus open lobectomy, P = .005; thoracoscopic wedge resection or lobectomy versus pneumonectomy, P = .021). In an exploratory approach, elevated IL-6 plasma peaks were associated with the occurrence of severe complications defined as Clavien-Dindo score grade ≥IVa during the postoperative phase up to 6 months after thoracic surgery ( P = .006). CONCLUSIONS: In summary, this substudy reveals factors, which correlate with high MCP-1 and IL-6 values. Moreover, higher IL-6 seems to be associated with postoperative severe complications. Perioperative IL-6 monitoring might be helpful for risk estimation in the perioperative setting of patients after lung surgery.